Persistent stromal fibroblast activation is present in chronic tendinopathy. Issue 1 (December 2017) - Dakin, Stephanie; Buckley, Christopher; Al-Mossawi, Mohammad Hussein; Hedley, Robert; Martinez, Fernando; Wheway, Kim; Watkins, Bridget; Carr, Andrew
Abstract Background Growing evidence supports a key role for inflammation in the onset and progression of tendinopathy. However, the effect of the inflammatory infiltrate on tendon cells is poorly understood. Methods We investigated stromal fibroblast activation signatures in tissues and cells from patients with tendinopathy. Diseased tendons were collected from well-phenotyped patient cohorts with supraspinatus tendinopathy before and after sub-acromial decompression treatment. Healthy tendons were collected from patients undergoing shoulder stabilisation or anterior cruciate ligament repair. Stromal fibroblast activation markers including podoplanin (PDPN), CD106 (VCAM-1) and CD248 were investigated by immunostaining, flow cytometry and RT-qPCR. Results PDPN, CD248 and CD106 were increased in diseased compared to healthy tendon tissues. This stromal fibroblast activation signature persisted in tendon biopsies in patients at 2–4 years post treatment. PDPN, CD248 and CD106 were increased in diseased compared to healthy tendon cells. IL-1β treatment induced PDPN and CD106 but not CD248. IL-1β treatment induced NF-κB target genes in healthy cells, which gradually declined following replacement with cytokine-free medium, whilstPDPN andCD106 remained above pre-stimulated levels. IL-1β-treated diseased cells had more profound induction ofPDPN andCD106 and sustained expression ofIL6 andIL8 mRNA compared to IL-1β-treated healthy cells. Conclusions We conclude that stromal fibroblast activation markers are increased and persist in diseased compared to healthy tendon tissues and cells. Diseased tendon cells have distinct stromal fibroblast populations. IL-1β treatment induced persistent stromal fibroblast activation which was more profound in diseased cells. Persistent stromal fibroblast activation may be implicated in the development of chronic inflammation and recurrent tendinopathy. Targeting this stromal fibroblast activation signature is a potential therapeutic strategy.